[Depression test] detect depression among college student using mobile application / Muhammad Asnawi Alias - Alias, Muhammad Asnawi (2018)
This research will introduce the overview about the depression among college student. The Problem statement, purpose and objective of the study are also discussed in order to get better understanding about the depression that occur in college student. This research also being done to know the effect depression toward the student environment and their student life. It is also being discussed the factor depression because of parent support, emotional distress and sleeping disorder. It will also include the research question that will assist and guide researcher to collect the accurate information about the depression on the student. The purpose of this project is to make a mobile application since people nowadays have their own smart phone and bring it anywhere.